Sprayed water-based lignin colloidal nanoparticle-cellulose nanofibril hybrid films with UV-blocking ability - Chen, Shouzheng; Harder, Constantin; Ribca, Iuliana; Sochor, Benedikt; Erbes, Elisabeth; Bulut, Yusuf; Pluntke, Luciana; Meinhardt, Alexander; Schummer, Bernhard; Oberthür, Markus; Keller, Thomas F; Söderberg, L. Daniel; et al. (Nanoscale advances, 2024)
In the context of global climate change, the demand for new functional materials that are sustainable and environmentally friendly is rapidly increasing. Cellulose and lignin are the two most abundant raw materials in nature, and are ideal components for functional materials. The hydrophilic interface and easy film-forming properties of cellulose nanofibrils make them excellent candidates for natural biopolymer templates and network structures. Lignin is a natural UV-shielding material, as it contains a large number of phenolic groups. In this work, we have applied two routes for spray deposition of hybrid films with different laminar structures using surface-charged cellulose nanofibrils and water-based colloidal lignin particles. As the first route, we prepare stacked colloidal lignin particles and cellulose nanofibrils hybrid film through a layer-by-layer deposition. As the second route, we spray-deposite premixed colloidal lignin particles and cellulose nanofibrils dispersion to prepare a mixed hybrid film. We find that cellulose nanofibrils act as a directing agent to dominate the arrangement of the colloidal lignin particles in a mixed system. Additionally, cellulose nanofibrils eliminate the agglomerations and thus increase the visible light transparency while retaining the UV shielding ability. Our research on these colloidal lignin and cellulose nanofibril hybrid films provides a fundamental understanding of using colloidal lignin nanoparticles as functional material on porous cellulose-based materials, for example on fabrics. UV shielding (blue arrow) and visible light transparency (visible light spectrum arrow) of the cellulose nanofibril/lignin colloid thin film are sketched. A SEM image with a sketch of the nanocomposite and hydrated lignin nanoparticle are shown.